Hubungan antara Kontak Erat dengan Anggota Keluarga Kasus Terkonfirmasi dan COVID-19 pada Anak di Puskesmas Panjatan II Kulon Progo - Anggita Bintari Handayaningrum; Tubagus Ferdi Fadilah (Fakultas Kedokteran Universitas Trisakti, 2022)
BackgroundIt is estimated that the positive infection rate of COVID-19 in Indonesia is 4.261.412 cases confirmed. Indonesian Pediatric Society noted that since May 2021, cases of pediatric COVID-19 infection have been rising; it is related to many factors such as host immunity, nutrition, sociodemographics, and close contact. Our research evaluated the closed contact factor with confirmed cases in a family member or household contact and pediatric COVID-19 infection, the incidence of pediatric COVID-19, the association between closed contact with confirmed cases in family members and pediatric COVID-19 infection. MethodsOur research uses the observational analytics method, cohort retrospective design, based on medical records, 242 samples collected, period November 2020-November 2021, with sampling technique consecutive nonrandom sampling; our inclusion criteria are 0-18 years old, have positive or negative antigen swab or RT-PCR, wholly followed up by the health center. ResultsUsing chi-square in SPSS application, our research stated Mother and Father are the main sources of household contact transmission, children 12-18 years old, women sex are the highest number the incidence, statistical result p<0,05. ConclusionsAccordingly, there is an association between closed contact with confirmed cases in family members and pediatric COVID-19 infection.